Gabinetti anatomici, fantocci e manuali: la formazione della levatrice nella storia sociale dell'educazione - Rossella Raimondo (Firenze University Press, 2020)
The intention behind this article is to shed light on the evolution of practices and theories related to the history of obstetrics, making particular reference to the places, devices and educational materials which became increasingly necessary to cope with the professionalization of individuals assigned to childbirth: female midwives and male surgeons. The approach here proposed intends to enhance the interdisciplinary intertwining and the multiple connections that, especially by relating the history of pedagogy with the history of obstetrics, fosters a broader vision of the implications relating to changes that have occurred over time.